2020
DOI: 10.1002/jsde.12398
|View full text |Cite
|
Sign up to set email alerts
|

The Application of a Nuclease Enzyme to Clean Stubborn Soils and Odors in Laundry

Abstract: The inclusion of a nuclease, a new‐to‐laundry enzyme class in detergent formulations, reduces the concentration of recalcitrant soils on dirty clothing. Nucleases target extracellular DNA that, albeit present in minor quantities in soiled laundry items, disproportionately contributes to the accumulation of sebaceous soils and other compounds that affect the appearance of clothes. These lingering soils accumulate over multiple wear cycles and provoke a dingy appearance in clothing, characterized by dull colors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 39 publications
4
8
0
Order By: Relevance
“…This eDNA not only serves as a source of nutrients for biofilm sustenance and growth 30 , but has recently been shown to have roles in the establishment and structural integrity of other biofilm components which contribute to recalcitrance of soils on textiles 6 , 31 . It is now becoming clear that eDNA is a critical component of the EPS matrix and that EPS on laundry are not efficiently being removed in current wash conditions, using non biological detergents to counteract these soils of microbial origin 18 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This eDNA not only serves as a source of nutrients for biofilm sustenance and growth 30 , but has recently been shown to have roles in the establishment and structural integrity of other biofilm components which contribute to recalcitrance of soils on textiles 6 , 31 . It is now becoming clear that eDNA is a critical component of the EPS matrix and that EPS on laundry are not efficiently being removed in current wash conditions, using non biological detergents to counteract these soils of microbial origin 18 .…”
Section: Discussionmentioning
confidence: 99%
“…40 °C for 30 min; typical European wash conditions), leave a lot of scope for improvement when it comes to tackling the sources of these undesirable characteristics 49 . Previous work has found that there are qualitative appearance benefits when adding DNase I for real consumer item cleaning; which translates into strong visual preferences for DNase I washed items 18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations